Right intraatrial lipoma. A case report - Arévalo-Santa-María, Azucena (2023)
We present the case of a 56-year-old male patient with a history of atrial flutter for six months; he was admitted to the hospital for presenting a mass of 8 cm in maximum diameter in the right atrium, which prolapsed through the tricuspid valve into the right ventricle. Emergency surgery was scheduled, performing exeresis of the tumor and tricuspid annuloplasty. The Pathological anatomy determined that the removed mass corresponded to a cardiac lipoma.